2022
DOI: 10.2147/dmso.s369809
|View full text |Cite
|
Sign up to set email alerts
|

Association of Higher Rates of Type 2 Diabetes (T2DM) Complications with Psychological and Demographic Variables: Results of a Cross-Sectional Study

Abstract: Introduction The aim of this study was to assess the relationship between the occurrence and number of T2DM complications with sociodemographic (age, sex, habitation, education), clinical (duration of diabetes, HbA1c (%), BMI) and psychological (well-being, sense of influence on the diabetes course, coping styles) variables. Methods A total of 2574 adult patients were assessed using The Sense of Influence on the Diabetes Course Scale, WHO-5 Well-Being Index, and the Bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Our previous ndings also suggest that depression and diabetes related distress interact to affect glycemic control. Another cross-sectional study even indicated that the score of WHO-5 was reversely correlated with the number of diabetes complications (43). A further longitudinal study is required to clarify the predictive validity of WHO-5 for glycemic control and diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous ndings also suggest that depression and diabetes related distress interact to affect glycemic control. Another cross-sectional study even indicated that the score of WHO-5 was reversely correlated with the number of diabetes complications (43). A further longitudinal study is required to clarify the predictive validity of WHO-5 for glycemic control and diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous findings also suggest that depression and diabetes-related distress interact to affect glycemic control. Another cross-sectional study even indicated that the score of WHO-5 was reversely correlated with the number of diabetes complications [ 45 ]. We assumed that the reason for this discrepancy may lie in that how the psychological state affects the physical indicators is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported the incidence and risk of complications according to the control status of patients diagnosed with HT or DM. In a recent study, patients with uncontrolled DM had 68% higher odds of developing micro- or macroangiopathy than those with controlled DM [ 12 ]. Furthermore, individuals with undiagnosed DM have poor long-term glycemic control and can die within a short time after the onset of complication-related symptoms [ 13 ].…”
Section: Introductionmentioning
confidence: 99%